Flame-retardant phase-change material and preparation method thereof
By introducing CNF/PNT skeletons and flame retardants into solid-liquid organic phase change materials, the problems of liquid leakage and low thermal conductivity are solved, and efficient electromagnetic shielding and flame retardant performance are achieved, which is suitable for the thermal management and electromagnetic shielding of electronic equipment.
Patent Information
- Application Number
- CN202510083529.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
AI Technical Summary
The problems of liquid leakage and low thermal conductivity during the phase change process of existing solid-liquid organic phase change materials lead to a reduced thermal management performance and a slowdown in charge and discharge speed.
The flame retardant phase change material was prepared by mixing and hybridizing cellulose nanofibers (CNF)/polypyrrole nanotubes (PNT) as the shape framework and thermal conductor, and polyethylene glycol, sunacid or octane as the phase change material, magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene as the flame retardant.
It has achieved a shape-stable phase change composite material with high thermal conductivity and high latent heat, with excellent electromagnetic shielding and flame retardant properties, which can effectively dissipate electromagnetic waves and exhibit significant flame retardant and drop-proof properties under high temperature conditions.
Smart Images

Figure CN119912780A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite phase change material design, synthesis and electromagnetic shielding, and relates to a flame retardant phase change material and a preparation method thereof. Background Art
[0002] In daily life, a large number of miniaturized and high-frequency communication electronic devices have emerged. Therefore, electromagnetic radiation has gradually become an important problem that people need to face. It will not only reduce the operating accuracy of the equipment, but also endanger human health. In order to solve these problems, electromagnetic interference (EMI) shielding materials have gradually attracted more and more attention. Usually, typical EMI shielding materials convert most of the electromagnetic radiation into heat. Continuous exposure to electromagnetic sources will cause a lot of heat accumulation, which may eventually cause equipment damage. Therefore, EMI materials need to solve the thermal management problem so that they can protect miniaturized and high-frequency electronic devices. This is consistent with the previous demand for thermal energy storage. This urgently requires the development of advanced electronic packaging materials that combine high EMI shielding and effective thermal management capabilities.
[0003] Solid-liquid organic phase change materials are considered ideal candidates due to their superior properties, including suitable phase change temperature, excellent chemical stability, non-toxicity, low corrosiveness, easy access, and negligible supercooling. However, the liquid leakage problem during the phase change process and low thermal conductivity are two long-standing fatal defects that have hindered their application. If these two problems are not properly solved, the liquefied phase change material (PCM) will leak and reduce the thermal management performance; insufficient thermal conductivity will reduce the charge and discharge speed. Summary of the invention
[0004] The purpose of the present invention is to overcome the disadvantages of the prior art and provide a flame retardant phase change material and a preparation method thereof. The phase change material has electromagnetic shielding and thermal management properties, and the preparation method is relatively simple.
[0005] To achieve the above-mentioned purpose, the present invention discloses a method for preparing a flame retardant phase change material, comprising: using CNF / PNT as a shape skeleton and a thermal conductor, mixing and hybridizing a phase change material, CNF / PNT and a flame retardant to obtain a flame retardant phase change material.
[0006] The further improvement of the method for preparing the flame retardant phase change material of the present invention is:
[0007] Furthermore, the phase change material is polyethylene glycol, decanoic acid or octadecane.
[0008] Furthermore, the flame retardant is a mixture of one or more of magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene.
[0009] Furthermore, the mass ratio of the phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0010] Further, the method specifically includes the following steps:
[0011] 1) Preparation of PNT framework;
[0012] 2) uniformly dispersing the phase change material and the cellulose nanofibers in deionized water to obtain a mixture A;
[0013] 3) preparing a uniform aqueous phase mixture of polyvinyl pyrrolidone and PNT skeleton, and then ultrasonically treating the mixture with an ultrasonic cell grinder, and adding a flame retardant to obtain a mixture B;
[0014] 4) Mixing the mixture A and the mixture B, stirring them, and then vacuum filtering them to obtain a PEG@CNF / PNT film, and then completely drying the PEG@CNF / PNT composite film to obtain a flame retardant phase change material.
[0015] Furthermore, the phase change material is polyethylene glycol, decanoic acid or octadecane;
[0016] The flame retardant is one or a mixture of multiple of magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene.
[0017] Further, the operation process of step 1) is:
[0018] Disperse methyl orange in deionized water to form a transparent orange methyl orange solution; disperse FeCl3 in deionized water to obtain a FeCl3 solution, pour the FeCl3 solution into the methyl orange solution to obtain a mixture of methyl orange and FeCl3; inject pyrrole into the mixture of methyl orange and FeCl3, stir at room temperature, and then filter to obtain a black product, wash and separate the black product, and finally dry it to obtain a PNT skeleton.
[0019] Furthermore, the mass ratio of polyvinyl pyrrolidone to PNT backbone is 3:1.
[0020] The invention discloses a flame retardant phase change material, which is prepared based on a preparation method of the flame retardant phase change material.
[0021] The flame retardant phase change material of the present invention is further improved in that:
[0022] Furthermore, the flame retardant phase change material is a film, solid powder or block.
[0023] The present invention has the following beneficial effects:
[0024] The flame-retardant phase-change material and preparation method thereof of the present invention are specifically operated by introducing PNT and CNF skeletons into PEG to prepare a shape-stable phase-change composite material PEG@CNF / PNT with high thermal conductivity and high latent heat, and on this basis, a layer of efficient flame retardant is attached on its surface for high-temperature flame retardant applications. At the same time, the phase-change composite material also has EMI shielding applications. The conductivity of PEG@CNF / PNT is 613S / m. In the x-band frequency range, the EMI SE of PEG@CNF / PNT is as high as 34.2dB, which is far better than the commercial standard of 20dB of most EMI SE materials, and it can effectively dissipate electromagnetic waves. In addition, due to the presence of flame retardants and PNT networks during the combustion process, SF / PNT exhibits significant flame retardant and drip-proof properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0026] Figure 1 It is a synthetic diagram of Example 1;
[0027] Figure 2 is the SEM image of sample PEG@CNF / PNT;
[0028] Figure 3 The front and back SEM images of the sample PEG@CNF / PNT;
[0029] Figure 4 This is the flexibility test diagram of the sample PEG@CNF / PNT;
[0030] Figure 5 Thermal conductivity diagram of sample PEG@CNF / PNT;
[0031] Figure 6 The conductivity diagram of the sample PEG@CNF / PNT;
[0032] Figure 7 This is the electromagnetic shielding performance diagram of the sample PEG@CNF / PNT;
[0033] Figure 8 This is the flame retardant performance diagram of sample PEG@CNF / PNT. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the description of the present invention, it should be understood that the terms “include” and “comprises” indicate the presence of described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or collections thereof.
[0036] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0037] It should be further understood that the term "and / or" used in the present specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects are in an "or" relationship.
[0038] It should be understood that, although the terms first, second, third, etc. may be used to describe preset ranges, etc. in the embodiments of the present invention, these preset ranges should not be limited to these terms. These terms are only used to distinguish preset ranges from each other. For example, without departing from the scope of the embodiments of the present invention, the first preset range may also be referred to as the second preset range, and similarly, the second preset range may also be referred to as the first preset range.
[0039] The word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining" or "in response to detecting", depending on the context. Similarly, the phrases "if it is determined" or "if (stated condition or event) is detected" may be interpreted as "when it is determined" or "in response to determining" or "when detecting (stated condition or event)" or "in response to detecting (stated condition or event)", depending on the context.
[0040] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0042] The method for preparing the flame retardant phase change material of the present invention comprises the following steps:
[0043] CNF / PNT is used as a shape skeleton and a thermal conductor, and the phase change material, the shape skeleton, the thermal conductor and the flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
[0044] Wherein, the phase change material is polyethylene glycol, decanoic acid or octadecane; the flame retardant is one or a mixture of multiple of magnesium hydroxide, decabromodiphenyl ether (DBDPO) and brominated polystyrene.
[0045] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0046] In this embodiment, the flame retardant phase change material is a film, solid powder or block.
[0047] Specifically, the method for preparing the flame retardant phase change material of the present invention comprises the following steps:
[0048] 1) Preparation of PNT framework;
[0049] 0.3437 g of methyl orange was dispersed in 100 mL of deionized water to form a transparent orange methyl orange solution; 2.8382 g of FeCl3 was dispersed in 100 mL of deionized water, mixed for 30 minutes to obtain a FeCl3 solution, and the FeCl3 solution was poured into the methyl orange solution to obtain a mixture of methyl orange and FeCl3; 0.728 mL of pyrrole was injected into the mixture of methyl orange and FeCl3, and then stirred at room temperature for 24 hours, and then filtered with deionized water and ethanol several times to obtain a black product, the black product was washed and separated, and finally dried in an oven at 80°C for 6 hours to collect the PNT product.
[0050] Preparation of composite membrane: Cellulose nanofiber / polypyrrole nanotube (PEG@CNF / PNT) composite membrane was prepared by vacuum filtration.
[0051] 1.2 g of polyethylene glycol (PEG) and 1.2 g of cellulose nanofibers (CNF) were uniformly dispersed in deionized water to obtain a mixture A;
[0052] According to the desired final PNT content, a uniform aqueous mixture of polyvinyl pyrrolidone (PVP, dispersant) and PNT skeleton in a mass ratio of 3:1 was prepared, and after ultrasonic treatment with an ultrasonic cell grinder, a predetermined amount of 30 wt% of flame retardant was added to obtain mixture B;
[0053] The mixture A and the mixture B were mixed and stirred, and then vacuum filtered to obtain a PEG@CNF / PNT membrane. Then, the PEG@CNF / PNT composite membrane was completely dried at 70°C.
[0054] Embodiment 1
[0055] Materials: Pyrrole (99%), FeCl3 (analytical grade (AR)), methyl orange (96%), Mg(OH)2 (AR, 95%), PEG-6000 (Mn = 6000 g / mol, 99% wt%) were all from Shanghai Aladdin Biochemical Technology Co., Ltd., cellulose nanofiber CNF was from Guilin Qihong Technology Co., Ltd., polyvinylpyrrolidone (PVP) and ethanol were provided by Sinopharm Chemical Reagent Co., Ltd., and organic nylon 6 filtration membrane (pore size 0.2 μm) was provided by Tianjin Jinteng Experimental Equipment Co., Ltd. All reagents were used directly without additional purification.
[0056] Preparation of PNT skeleton: first, disperse 0.3437 g of methyl orange in 100 mL of deionized water to form a transparent orange methyl orange solution; disperse 2.8382 g of FeCl3 in 100 mL of deionized water, mix for 30 minutes to obtain a FeCl3 solution, pour the FeCl3 solution into the methyl orange solution, then add 0.728 mL of pyrrole, stir at room temperature for 24 hours, and then filter with deionized water and ethanol several times to obtain a black product, wash and separate the black product, and finally dry it in an oven at 80°C for 6 hours to obtain a PNT skeleton.
[0057] Preparation of composite membrane: Cellulose nanofiber / polypyrrole nanotube (PEG@CNF / PNT) composite membrane was prepared by vacuum filtration. 1.2 g of polyethylene glycol (PEG) and 1.2 g of cellulose nanofiber (CNF) were uniformly dispersed in deionized water to obtain mixture A; according to the desired final PNT content, a uniform aqueous phase mixture of polyvinyl pyrrolidone (PVP, dispersant) and PNT with a mass ratio of 3:1 was obtained, and then after ultrasonic treatment with an ultrasonic cell grinder, a predetermined amount of 30 wt% of flame retardant was added to obtain mixture B, and mixture A and mixture B were mixed and stirred, and then vacuum filtered to obtain PEG@CNF / PNT composite membrane, and then the PEG@CNF / PNT composite membrane was completely dried at 70°C.
[0058] Embodiment 1
[0059] The preparation process of the PEG@CNF / PNT composite membrane described in this embodiment is as follows:
[0060] 0.3437 g of methyl orange was dispersed in 100 mL of deionized water to obtain a transparent orange methyl orange solution; 2.8382 g of FeCl3 was dispersed in 100 mL of deionized water and mixed for 30 minutes to obtain a FeCl3 solution, the FeCl3 solution was poured into the methyl orange solution, and then 0.728 mL of pyrrole was injected, stirred at room temperature for 24 hours, and then filtered with deionized water and ethanol several times to obtain a black product, the black product was washed and separated, and finally dried in an oven at 80°C for 6 hours to obtain a PNT product.
[0061] Preparation of composite membrane: A cellulose nanofiber / polypyrrole nanotube (PEG@CNF / PNT) composite membrane was prepared by vacuum filtration. Specifically, 1.2 g of polyethylene glycol (PEG) and 1.2 g of cellulose nanofiber (CNF) were uniformly dispersed in deionized water to obtain a mixture A; according to the required final PNT content, a uniform aqueous phase mixture of polyvinyl pyrrolidone (PVP, dispersant) and PNT in a mass ratio of 3:1 was obtained, and then after ultrasonic treatment with an ultrasonic cell grinder, 30 wt% of flame retardant Mg(OH)2 was added to obtain a mixture B. The mixture A and the mixture B were mixed and stirred, and then vacuum filtered to obtain a PEG@CNF / PNT composite membrane, and the PEG@CNF / PNT composite membrane was completely dried at 70°C.
[0062] Application of the obtained PEG@CNF / PNT: The prepared composite film is coated on an electrical appliance (battery), and the temperature change is monitored by a thermocouple temperature measuring device. The real-time temperature, average temperature, and temperature difference under different working environments are obtained to characterize the thermal management performance. The electromagnetic shielding efficiency is tested by a vector network analyzer VNA, and its flame retardant performance is verified by an alcohol lamp.
[0063] Embodiment 2
[0064] This example is used to prepare PEG@MXene; the difference between this example and Example 1 is that the skeleton mixed solution (PNT and CNF) in Example 1 is replaced with 50 ml of Ti3AlC2 solution, and the rest of the method is the same as that described in Example 1.
[0065] The obtained PEG@MXene is used in practical applications as follows: the PEG@CNF / PNT in Example 1 is replaced by PEG@MXene, and the other methods are the same as those described in Example 1.
[0066] Embodiment 3
[0067] This example is used for the preparation of CA (caprylic acid) @CNF / PNT; the difference between this example and Example 1 is that 1.2 g of PEG in Example 1 is replaced by 1.2 g of CA, and the rest of the method is the same as that in Example 1.
[0068] The obtained CA@CNF / PNT is applied in practice as follows: the PEG@CNF / PNT in Example 1 is replaced by CA@CNF / PNT, and the other methods are the same as those described in Example 1.
[0069] Embodiment 4
[0070] This example is used for the preparation of LA (dodecanol) @CNF / PNT. The difference between this example and Example 1 is that 1.2 g of PEG in Example 1 is replaced with 1.2 g of dodecanol, and the rest of the method is the same as that described in Example 1.
[0071] The obtained dodecanol@CNF / PNT is used in practical applications as follows: the PEG@CNF / PNT in Example 1 is replaced with dodecanol@CNF / PNT, and the other methods are the same as those described in Example 1.
[0072] Embodiment 5
[0073] This example is used for the preparation of NO (n-octadecane) @CNF / PNT. The difference between this example and Example 1 is that 1.2 g of PEG in Example 1 is replaced with 1.2 g of octadecane, and the rest of the method is the same as that described in Example 1.
[0074] The obtained octadecane@CNF / PNT is used in practical applications as follows: the PEG@CNF / PNT in Example 1 is replaced with octadecane@CNF / PNT, and the other methods are the same as those described in Example 1.
[0075] Embodiment 6
[0076] This example is used for the preparation of PEG@CNF / PNT / BPS (brominated polystyrene). The difference between this example and Example 1 is that 30 wt % of the flame retardant Mg(OH)2 in Example 1 is replaced by BPS; the rest of the method is the same as that described in Example 1.
[0077] The obtained PEG@CNF / PNT / BPS is applied in practice as follows: the PEG@CNF / PNT in Example 1 is replaced by PEG@CNF / PNT / BPS, and the other methods are the same as those described in Example 1.
[0078] Comparative Example 1
[0079] For the preparation of CNF / PNT, the difference between this comparative example and Example 1 is that PEG and flame retardant Mg(OH)2 are not added, and the rest of the method is the same as that described in Example 1.
[0080] refer to Figure 2 , Figure 2 This is the SEM image of the classic cross-section of the PEG@CNF / PNT membrane.
[0081] refer to Figure 3 , which shows the digital photos and SEM photos of the front and back of the PEG@CNF / PNT composite membrane, respectively. The front and back are conductive networks composed of CNF / PNT, and there is no obvious difference between them. In view of this, continuous vacuum filtration can form a thermally and electrically conductive network in the CNF / PNT substrate and enhance the ability to use SF / PNT composite membranes for battery thermal management (BTM).
[0082] refer to Figure 4 ,from Figure 4 It can be seen that the composite film has a certain flexibility, which provides the possibility for packaging materials of electronic components.
[0083] refer to Figure 5 , TC characterization of CNF / PNT and PEG@CNF / PNT is as follows Figure 5 As shown in the figure, the TCs measured in the thermal constant analyzer were 0.26, 0.39, 0.59 and 0.92 W / m·K, respectively. When the PNT addition amount was 10wt%, the TC reached 0.92 W / m·K, which was about 254% higher than that of pure CNF / PNT. The reason for the improvement is that the PNT with excellent TC is evenly dispersed in the PEG matrix as a skeleton, forming a perfect three-dimensional heat conduction mode in the composite material.
[0084] refer to Figure 6 , as the PNT content increases, the conductivity of the PEG@CNF / PNT composite film increases, and the accompanying light-emitting diode (LED) bulb becomes brighter. When the PNT content is 10wt%, the conductivity of the PEG@CNF / PNT composite film reaches 613S / m. This is due to the fact that the PNT is evenly dispersed on the composite film, forming a fully functional conductive network under the uniform dispersion of CNF, thus providing the composite film with excellent conductivity. The excellent conductivity makes it possible for the PEG@CNF / PNT composite film to have good EMI SE. The electromagnetic interference shielding performance was studied.
[0085] refer to Figure 7 , it can be seen that as the PNT content increases from 2.5wt% to 10wt%, the EMI SE of PEG@CNF / PNT in the x-band increases from 0.2dB to 34.2dB, and is independent of the test frequency. This is because CNF / PNT affects the formation of the PEG@CNF / PNT conductive network. Therefore, the construction of the architecture is an effective strategic approach to improve the EMI SE behavior of the material.
[0086] refer to Figure 8, an alcohol burner was used for the combustion study, and the sample was ignited on the fire for one second and then moved away from the flame. The CNF / PNT sample burned severely 1s after ignition until finally all the membranes burned to ash. The PEG sample did not burn when it was close to the flame, but continued to melt and drip. Importantly, the PEG@CNF / PNT film quickly self-extinguished after burning, and the PEG@CNF / PNT composite film burned completely without any melt dripping, and the film structure remained intact after burning, indicating that PEG@CNF / PNT has great anti-leakage potential. When Mg(OH)2 is heated, it releases H2O and absorbs a large amount of heat, which increases the sample temperature, while playing a flame retardant role under the dual effect of CNF / PNT. In summary, PEG@CNF / PNT exhibits excellent thermal stability and flame retardancy throughout the process.
[0087] Embodiment 7
[0088] The method for preparing the flame retardant phase change material of the present invention comprises: using CNF / PNT as a shape skeleton and a heat conductor, mixing and hybridizing the phase change material, CNF / PNT and a flame retardant to obtain the flame retardant phase change material.
[0089] In this embodiment, the phase change material is capric acid.
[0090] In this embodiment, the flame retardant is brominated polystyrene.
[0091] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0092] Embodiment 8
[0093] and a thermal conductor, and the phase change material, CNF / PNT and a flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
[0094] In this embodiment, the phase change material is octadecane.
[0095] In this embodiment, the flame retardant is decabromodiphenyl ether.
[0096] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0097] Embodiment 9
[0098] and a thermal conductor, and the phase change material, CNF / PNT and a flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
[0099] In this embodiment, the phase change material is polyethylene glycol.
[0100] In this embodiment, the flame retardant is magnesium hydroxide.
[0101] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0102] Embodiment 10
[0103] and a thermal conductor, and the phase change material, CNF / PNT and a flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
[0104] In this embodiment, the phase change material is capric acid.
[0105] In this embodiment, the flame retardant is a mixture of decabromodiphenyl ether and brominated polystyrene.
[0106] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0107] Embodiment 11
[0108] and a thermal conductor, and the phase change material, CNF / PNT and a flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
[0109] In this embodiment, the phase change material is polyethylene glycol.
[0110] In this embodiment, the flame retardant is a mixture of magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene.
[0111] In this embodiment, the mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
[0112] Compared with the prior art, the present invention improves the synthesis method of the composite phase change film, so that the phase change film has certain mechanical properties, excellent thermal stability, good electromagnetic shielding performance and excellent thermal management ability. The synthesis method is simple to operate, convenient, low-cost, suitable for large-scale production, has significant green and economic benefits, and can be widely used in the fields of thermal management and electromagnetic shielding of various types of electronic instruments.
[0113] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and disclosure of the invention. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0114] It should be understood that the present invention is not limited to the exact construction that has been described above and shown in the drawings and that various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
[0115] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural change made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a flame retardant phase change material, characterized in that: include: CNF / PNT is used as a shape skeleton and a thermal conductor, and a phase change material, CNF / PNT and a flame retardant are mixed and hybridized to obtain a flame retardant phase change material.
2. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: The phase change material is polyethylene glycol, decanoic acid or octadecane.
3. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: The flame retardant is one or a mixture of multiple of magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene.
4. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: The mass ratio of phase change material, CNF / PNT and flame retardant is 4-5:3-4:1-3.
5. The method for preparing a flame retardant phase change material according to claim 1, characterized in that: The specific steps include: 1) Preparation of PNT framework; 2) uniformly dispersing the phase change material and the cellulose nanofibers in deionized water to obtain a mixture A; 3) preparing a uniform aqueous phase mixture of polyvinyl pyrrolidone and PNT skeleton, and then ultrasonically treating the mixture with an ultrasonic cell grinder, and adding a flame retardant to obtain a mixture B; 4) Mixing the mixture A and the mixture B, stirring them, and then vacuum filtering them to obtain a PEG@CNF / PNT film, and then completely drying the PEG@CNF / PNT composite film to obtain a flame retardant phase change material.
6. The method for preparing a flame retardant phase change material according to claim 5, characterized in that: The phase change material is polyethylene glycol, decanoic acid or octadecane; The flame retardant is one or a mixture of multiple of magnesium hydroxide, decabromodiphenyl ether and brominated polystyrene.
7. The method for preparing a flame retardant phase change material according to claim 5, characterized in that: The operation process of step 1) is: Disperse methyl orange in deionized water to form a transparent orange methyl orange solution; disperse FeCl3 in deionized water to obtain a FeCl3 solution, pour the FeCl3 solution into the methyl orange solution to obtain a mixture of methyl orange and FeCl3; inject pyrrole into the mixture of methyl orange and FeCl3, stir at room temperature, and then filter to obtain a black product, wash and separate the black product, and finally dry it to obtain a PNT skeleton.
8. The method for preparing a flame retardant phase change material according to claim 6, characterized in that: The mass ratio of polyvinyl pyrrolidone to PNT backbone is 3:
1.
9. A flame retardant phase change material, characterized in that: The flame retardant phase change material is prepared based on the preparation method of any one of claims 1 to 8.
10. The flame retardant phase change material according to claim 9, characterized in that: The flame retardant phase change material is in the form of a film, solid powder or block.